Energy Plantations in Arunachal Pradesh - Choudhury, J. M. (Indian Forester, 1981)
Firewood is the chief of source of energy in Arunchal Pradesh. The entire quantity of fuelwood is collected from the adjoining forests by the villagers as a matter of traditional right. The use of gobar gas plant is uneconomical because of the lower temperatures prevailing in major portions of the year. The anticipated requirement of fulewood for 1990 and 2OOO is of the order of 5.88 and 8.23 million m3 , respectively. Though the present fuelwood requirements have not attained critical dimensions, the hacking of forests in and around the habitations is creating serious environmental problems. Programmes have been initiated for raising energy plantations in Arunachal Pradesh. An outline of the programmes underway and projects proposed are presented. The main problem in implementation are inadequacy of funds. The removal of this constraint will help in solving the anticipated energy crisis in this area at the same time affording sufficient environmental protection.